Towards Networked Learning Analytics - A Concept and a Tool - Retalis, S.; Papasalouros, A.; Psaromiligkos, Y.; Siscos, S.; Kargidis, T. (Proceedings of the International Conference on Networked Learning, 2006)
Networked learning is much more ambitious than previous approaches of ICT-support in education. It is therefore more difficult to evaluate the effectiveness and efficiency of the networked learning activities. Evaluation of learners' interactions in networked learning environments is a difficult, resource and expertise demanding task. Educators participating in online learning environments, have very little support by integrated tools to evaluate students' activities and identify learners' online browsing behavior and interactions. As a consequence, educators are in need for non-intrusive and automatic ways to get feedback from learners' progress in order to better follow their learning process and appraise the online course effectiveness. They also need specialized tools for authoring, delivering, gathering and analysing data for evaluating the learning effectiveness of networked learning courses. Thus, the aim of this paper is to propose a new set of services for the evaluator and lecturer so that he/she can easily evaluate the learners' progress and produce evaluation reports based on learners' behaviour within a Learning Management System. These services allow the evaluator to easily track down the learners' online behavior at specific milestones set up, gather feedback in an automatic way and present them in a comprehensive way. The innovation of the proposed set of services lies on the effort to adopt/adapt some of the web usage mining techniques combining them with the use of semantic description of networked learning tasks